2021
DOI: 10.1021/acscatal.1c00131
|View full text |Cite
|
Sign up to set email alerts
|

Flame Synthesis of Cu/ZnO–CeO2 Catalysts: Synergistic Metal–Support Interactions Promote CH3OH Selectivity in CO2 Hydrogenation

Abstract: The hydrogenation of CO 2 to CH 3 OH is an important reaction for future renewable energy scenarios. Herein, we compare Cu/ZnO, Cu/CeO 2 , and Cu/ZnO–CeO 2 catalysts prepared by flame spray pyrolysis. The Cu loading and support composition were varied to understand the role of Cu–ZnO and Cu–CeO 2 interactions. CeO 2 addition improves Cu dispersion with respect to ZnO, owing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 84 publications
6
43
0
Order By: Relevance
“…1d) shows that C, N, Co and Zn elements are uniformly distributed throughout the particles and can overlap in the catalyst, indicating that the prepared material is a homogeneous bimetallic structure. 30,31 The absence of the Zn crystal lattice, consistent with the later XRD result, could be attributed to the low content and ultrafine size, 32 but its existence can be confirmed by EDS, ICP-OES (Table S2†) and XPS analysis (Fig. 2b).…”
Section: Resultssupporting
confidence: 75%
“…1d) shows that C, N, Co and Zn elements are uniformly distributed throughout the particles and can overlap in the catalyst, indicating that the prepared material is a homogeneous bimetallic structure. 30,31 The absence of the Zn crystal lattice, consistent with the later XRD result, could be attributed to the low content and ultrafine size, 32 but its existence can be confirmed by EDS, ICP-OES (Table S2†) and XPS analysis (Fig. 2b).…”
Section: Resultssupporting
confidence: 75%
“…Hensen et al. reported enhanced catalytic activity and CH 3 OH selectivity over a ternary Cu/ZnO/CeO 2 catalyst compared to Cu/ZnO because the Cu/CeO 2 interfaces inhibit the RWGS reaction . In addition, SMSI can be used to improve the stability of catalysts, which is of vital importance in industrial application. , Several papers investigated the reasons for deactivation of the Cu/ZnO system, and structural changes of ZnO are ascribed to the main cause. The stability of the catalyst can be enhanced by the partial decoration of metal nanoparticles by the support overlayer via the SMSI.…”
Section: Application Of Smsi In Catalyst Designmentioning
confidence: 99%
“…The difference lies in the facile desorption of CO over Pt/TiO 2 and Pt/SiO 2 catalysts, leading to high selectivity of CO. 142 Hensen et al reported enhanced catalytic activity and CH 3 OH selectivity over a ternary Cu/ZnO/CeO 2 catalyst compared to Cu/ZnO because the Cu/CeO 2 interfaces inhibit the RWGS reaction. 143 In addition, SMSI can be used to improve the stability of catalysts, which is of vital importance in industrial application. 144,145 Several papers investigated the reasons for deactivation of the Cu/ZnO system, and structural changes of ZnO are ascribed to the main cause.…”
Section: Application Of Smsi In Catalyst Designmentioning
confidence: 99%
“…Nature (Brønsted or Lewis), acid strength (weak to moderate) as well as the textural properties (mesoporosity) of acidic sites play a basic role in the performance of methanol dehydration. Various catalysts for CO2 hydrogenation have been investigated, including [69][70][71][72][73][74][75][76], Pd-based catalysts [77][78][79][80], and bimetallic catalysts such as Pd-Ni, Fe-Ni, Ni-Ti, and Pd-Zn as effective couple for methanol production [81][82][83][84][85]. Among these catalysts, Cu-ZnO-based catalysts are the most widely used [86][87][88][89][90] because the Cu and ZnO loadings play a critical role in the physicochemical properties and catalytic performance of catalysts [91].…”
Section: Bifunctional Hybrid Catalystsmentioning
confidence: 99%